The efficacy of small molecule anti-angiogenic drugs in previously treated Thymic carcinoma - Yelan Guan; Xiaodong Gu; Jinfei Si; Jing Xiang; Jingwen Wei; Yue Hao; Wenxian Wang; Yan Sun (BMC Cancer, 2023)
Abstract Background Antiangiogenic drugs have shown initial efficacy in the treatment of advanced thymic carcinomas (TCs); however, data are limited. In this study, we provide real-world data relating to the efficacy of antiangiogenic drugs for the treatment of patients with TCs. Methods We retrospectively collected data on clinical progress after first-line chemotherapy in TCs patients who were treated with small molecule antiangiogenic drugs at our institution between January 2010 and December 2021. Tumor response was evaluated according to version 1.1 of the Response Evaluation Criteria in Solid Tumors. Progression free survival and overall survival were calculated using the Kaplan-Meier method. Results Of the 17 patients enrolled, 13 (76.5%) received apatinib and four (23.5%) anlotinib monotherapy with an objective response rate of 23.5%. Eleven (64.7%) patients had stable disease. The median follow-up period was 46.0 months (95% confidence interval [CI], 33.0–59.0 months). The median progression survival and overall survival were 7.9 months (95% CI, 6.5–9.3) and 47.0 months (95% CI, 35.4–58.6), respectively. In the 13 patients receiving apatinib, the median PFS was 7.0 months (95% CI, 5.0–9.0), compared with 8.0 months (95% CI, 2.7–13.3 months) for patients in the anlotinib group (P = 0.945). The most common grade 3 adverse events (AEs) were hypertension (n = 3, 23.1%), followed by proteinuria and hand-foot syndrome (HFS, n = 2, 15.4%). There were no grade 4 AEs although eight patients (47.1%) required mid-course discontinuation. Conclusion For refractory TCs, small molecule antiangiogenic drugs are efficacious as second- or post-line treatments. The toxicity of antiangiogenic therapy is manageable.